2013
DOI: 10.5051/jpis.2013.43.6.308
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dentists' subjective satisfaction with a newly developed device for maxillary sinus membrane elevation by the crestal approach

Abstract: PurposeThe purposes of this study were to assess the dentists' subjective satisfaction with the crestal approach sinus (CAS) kit, a device for maxillary sinus membrane elevation by the crestal approach using a special drilling system and hydraulic pressure, and to summarize the subjective satisfaction of dental implants placed after a sinus lift procedure with the CAS kit.MethodsThirty dental clinicians who had experience with dental implant placement after a sinus lift procedure with the CAS kit from June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…This percentage is smaller than that reported in our study (8.3%); however, we believe that our method of checking perforations is more accurate. Also, the difference in sample size may have contributed to the outcome [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This percentage is smaller than that reported in our study (8.3%); however, we believe that our method of checking perforations is more accurate. Also, the difference in sample size may have contributed to the outcome [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 ) and the saline solution is injected. 0.30 mL can elevate the membrane up to 3 mm [ 5 ]. The saline is drown out then injected again until the desired elevation is reached.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey by Young-Kyun Kim, Yong-Seok Cho and Pil-Young Yun, it was revealed that the satisfaction levels of dentists using a crestal approach sinus elevation kit was around 92.9% to approach the sinus floor but 25% did not use the hydraulic lifter provided thus indicating a mix of techniques employed in practice [17].…”
Section: (F) Another Innovative Crestal Technique Based On Highmentioning
confidence: 99%
“…To overcome these problems, instruments designed to grind the bone without perforating the membrane—rather than fracturing the maxillary cortical bone via mallet tapping—have been developed [6, 17, 18]. Compared with traditional methods, this method reportedly confers advantages to both the operator and the patient, as it is simple to perform and is associated with fewer postoperative complications [17, 19, 20].…”
Section: Introductionmentioning
confidence: 99%